1999
DOI: 10.1007/s007010050279
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding Risk in Unruptured and Residual Cerebral Aneurysms - Angiographic Annual Growth Rate in Nineteen Patients

Abstract: Whether and when unruptured aneurysms or aneurysmal rests following incomplete surgery result in subsequent bleeding are major concerns for neurosurgeons. By calculating the annual growth rate of aneurysms in long-term follow-up angiography (partly supplemented with MR-imaging and/or MR-angiography), we attempted to determine the surgical indications for these aneurysms. Long-term follow-up angiography ranging from one to 20 years was carried out on five patients whose ruptured aneurysms had been incompletely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 27 publications
0
23
1
Order By: Relevance
“…Even though the size of the aneurysm is currently used as an indicator to determine the risk of rupture, it has been suggested that the growth rate of the aneurysm may also be a strong indicator of the rupture risk (Imaizumi et al, 2002;Kamitani et al, 1999). The growth rate of the present model aneurysm depends strongly on the life-time of the collagen fibres.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 91%
See 1 more Smart Citation
“…Even though the size of the aneurysm is currently used as an indicator to determine the risk of rupture, it has been suggested that the growth rate of the aneurysm may also be a strong indicator of the rupture risk (Imaizumi et al, 2002;Kamitani et al, 1999). The growth rate of the present model aneurysm depends strongly on the life-time of the collagen fibres.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 91%
“…Yamaki et al (1986), for example, report about a cerebral aneurysm that enlarged from 2 mm to 15 mm in only 24 days, whereas Imaizumi et al (2002) report of an aneurysm that grew from about 4 mm to 10 mm in one year. Kamitani et al (1999) study the growth rate of a large population of unruptured cerebral saccular aneurysms. They report growth rates ranging from 1% up to 120% of size increase per year.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…1,4,19,20) Additionally, the infundibulum of the PCoA partly implanted into the neck may prevent complete obliteration. 20) Many cases of regrowth and rerupture have been reported after clipping of ICA-PCoA aneurysms, 4,11,16,19,21) although the incidence of aneurysm remnants at this location differs. 14,16,18,20) Third, the present study included a thorough search for aneurysm remnants using endoscopy during surgery, especially around the blind corner between the aneurysm and its parent artery.…”
Section: Discussionmentioning
confidence: 99%
“…24) Aneurysm remnants after clipping may regrow and lead to recurrent symptoms of hemorrhage or mass effect. 4,5,[7][8][9]11,14,[16][17][18][19][20][21]24) Therefore, aneurysm surgery should aim at complete circulatory exclusion of aneurysms, but this cannot be achieved in several circumstances including large necks, insufficient exposure, and mal-positioning of clips. 4,7,9,20) Aneurysm remnants can be classified into two groups, dog-ear and broad-based remnant.…”
Section: Introductionmentioning
confidence: 99%
“…75) The residual neck after surgical clipping sometimes carries the risks of enlargement and rupture. 9,27,37,64,69) The incidence of neck residuals in postoperative angiographic series has been reported as 5-9%. 9,62,69) Technical advances in diagnostic tools enable more precise postoperative evaluation of surgical clipping.…”
Section: Pathology Of Ruptured Aneurysmsold and Recent Knowledgementioning
confidence: 99%